Retentive forces, tensile strength and deflection fatigue of Acetal thermoplastic clasp material in comparison with cobalt-chromium alloy - Alwan, Samar S; Ismail, Intisar J (Journal of Baghdad College of Dentistry, 2014)
Background: Nowadays there is an increasing of the emphasis on aesthetic, dentist have been concerned about providing aesthetics and functional removable partial dentures to their patients and this was make the mission more difficult because of the goal now is achieving optimal aesthetic of the denture - while maintaining retentive, stable, and conservative to the health of supporting tooth and supporting tissue. The traditional use of metal clasp like cobalt-chromium, gold, stainless-steel and titanium hampers esthetics because of its obvious display conflicts with patient’s prosthetic confidentiality. Acetal resin (poly oxy methylene) may be used as alternative denture clasp material. This material was promoted primarily on the basis of its superior esthetic. Material and method: In this study, Acetal resin of Flexite and co-cr alloy of Wirocast companies were used. Four metal models of two premolars and two molars were surveyed to have 0.25mm and 0.5mm undercut depth for each one of the materials. eighty clasps were prepared and tested by testing machine to measure the load required to dislodge Acetal and co-cr clasps of 2mm. thickness (for premolar and molar). Tensile test were utilized for both Acetal resin and co-cr. tensile values will be used in special formula to calculate the amount of deflection. Results: The results of this study revealed that Acetal resin clasp of molar with 0.5mm undercut depth have the higher retentive force, and premolar with 0.25 mm undercut depth have the lowest retentive force as compared to co-cr. Also Acetal had lower values of the tensile strength as compared to co-cr alloy but it had higher deflection value than co-cr and it can withstand higher deflections than those of co-cr before having permanent deformation or fracture Conclusions: Acetal resin can be used with limitation as an alternative to co-cr alloy clasps in removable partial dentures.